Thermosetting bismaleimide resins generating covalent and multiple hydrogen bonds. Issue 11 (20th November 2015) - Shibata, Mitsuhiro; Satoh, Kazuki; Ehara, Shouta
ABSTRACT: Prepolymerizations of 4, 4′‐bismaleimidodiphenylmethane (BMI), diallyl isocyanurate (DAIC), and melamine (ML) at 160–170°C and subsequent compression molding at 200–280°C yielded cured BMI/DAIC/ML resins with feed molar ratios of 4/1/1, 3/1/1, and 2/1/1 (BMI‐DAIC‐ML411, 311, and 211). Similarly, cured BMI/DAIC 1/1 and BMI/ML 3/1 resins (BMI‐DAIC11 and BMI‐ML31) were prepared. The FT‐IR analysis revealed that the maleimide and allyl groups were almost consumed for all the cured resins, and the hydrogen bonding interaction became stronger with decreasing BMI contents for BMI‐DAIC‐MLs. Based on the cured structures elucidated from the FT‐IR result, the numbers of multiple hydrogen bonds and cross‐linking covalent bonds ( N MHB and N CB ), and total cross‐linking bond energy ( E TB ) were evaluated to be 0, 7.92, and 618 for BMI‐DAIC‐ML411, 0.71, 7.81, and 627 for BMI‐DAIC‐ML311, and 0.95 mol kg −1, 7.61 mol kg −1, and 617 kcal kg −1 for BMI‐DAIC‐ML211, respectively. A higher order of glass transition and 5% weight loss temperatures for BMI‐DAIC‐MLs was 411 > 311 > 211 in accordance with a higher order of N CB . BMI‐DAIC‐MLs displayed a weak tan δ peak at 70–150°C due to dissociation of the hydrogen bonds. The flexural strength and modulus of BMI‐DAIC‐ML311 were higher than those of BMI‐DAIC‐ML411 in accordance with the difference of E TB . © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43121. Abstract :